Application of Fuzzy Logic For Feasibility Evaluation of Pasteurized Milk Consumption Based On Processing Temperature and pH - Nauval Artyasta; Wuliddah Tamsil Barokah; Annisa Raihanah Maimun; Mrr. Lukie Triniawati; Phasya Laila Safitri; Indah Puji Lestari; Fawziya Nusa Hrishita; Priskila Margaretha Sibagariang; Fila Adida Pranata; Fathan Ahmad Munawwar; Roma Juliana Arios (Batrisya Education, 2026)
This study utilizes a fuzzy logic approach to analyze the consumption feasibility of pasteurized milk, focusing on the interplay between temperature and pH as key quality indicators. Given milk's perishable nature and the inherent imprecision of conventional monitoring methods, fuzzy logic provides a more adaptive and realistic assessment system. The Mamdani fuzzy system employed involves fuzzification, inference, and defuzzification to convert temperature and pH data into a quantifiable crisp output. Results, validated by the Fuzzy Control Surface and Centroid calculation (Sample 1: Temp 63, pH 5.4), demonstrate that the highest risk of damage occurs when low temperature combines with acidic (low) pH, leading to an